Fostering Student Well-Being in Online Physics Learning through the Integration of Social Cure and Adaptive Learning - Asyhari, Ardian; Islamia, Intan (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study investigates integrating Social Cure strategies and Adaptive Learning technologies to foster student well-being in online physics education. Employing a convergent mixed-methods design with 112 first-year undergraduates enrolled in a Basic Physics course at Universitas Islam Negeri Raden Intan Lampung during the 2022/2023 academic year, the research combined validated instruments (WEMWBS, PSSM, GSE-6, OSE, AEQ-S, Paas scale) with thematic interview analysis. Quantitative findings revealed significant increases in well-being, belonging, self-efficacy, and engagement, alongside reductions in cognitive load and anxiety. At the same time, qualitative narratives confirmed that peer mentoring, identity-building, and adaptive scaffolding synergistically enhanced emotional security and academic confidence. Confirmatory factor analysis supported the reliability and validity of measurement models, and joint displays integrated statistical results with students lived experiences. The study extends Social Cure theory into Physics contexts and enriches Cognitive Load Theory by demonstrating the dual benefits of socio-emotional support and adaptive personalization. It offers a replicable model for higher education institutions to design inclusive online environments that balance intellectual rigor with psychological well-being. It provides actionable insights for curriculum reform and digital pedagogy in Physics education.